2019
DOI: 10.1002/cmdc.201900281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nitrogen‐Containing Goniothalamin Analogues with Higher Cytotoxic Activity and Selectivity against Cancer Cells

Abstract: Two series of racemic goniothalamin analogues displaying nitrogen‐containing groups were designed and synthesized. A total of 19 novel analogues were evaluated against a panel of four different cancer cell lines, along with the normal prostate cell line PNT2 to determine their selectivity. Among them, goniothalamin chloroacrylamide 13 e displayed the lowest IC50 values for both MCF‐7 (0.5 μm) and PC3 (0.3 μm) cells, about 26‐fold more potent than goniothalamin (1). Besides its higher potency, compound 13 e als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…GTN@Ac-Dex NPs were dispersed in either 3% Tween 80 in 0.1 M acetate buffer (pH 5.5) or 3% Tween 80 in 0.01 M PBS buffer (pH 7.4) and incubated at 37 °C under gentle shaking. At specified time points (2,4,6,8,12,24,48,72, and 96 h), the whole suspension was centrifuged at 11 300g for 20 min to separate the pellet from the supernatant. The supernatant was withdrawn for analysis and replaced with an equal volume of the fresh buffer solution containing 3% Tween 80, in which the pellet was resuspended and returned for further incubation.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…GTN@Ac-Dex NPs were dispersed in either 3% Tween 80 in 0.1 M acetate buffer (pH 5.5) or 3% Tween 80 in 0.01 M PBS buffer (pH 7.4) and incubated at 37 °C under gentle shaking. At specified time points (2,4,6,8,12,24,48,72, and 96 h), the whole suspension was centrifuged at 11 300g for 20 min to separate the pellet from the supernatant. The supernatant was withdrawn for analysis and replaced with an equal volume of the fresh buffer solution containing 3% Tween 80, in which the pellet was resuspended and returned for further incubation.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Styryl lactones comprise a group of plant-derived compounds displaying a wide spectrum of biological properties, including antineoplastic activity. Among the bioactive styryl lactones, one of the most widely studied is goniothalamin (GTN), which can be isolated from Goniothalamus species within the Annonaceae family. ,,, The increasing interest in the pharmacological profile of GTN over the last years stems from its antiproliferative and cytotoxic effects toward a variety of human tumor cells and the recently demonstrated antitumor activity in mouse tumor models. ,, Previous studies from our group have shown that not only the naturally occurring ( R )-isomer is cytotoxic but the synthetic ( S )- and racemic ( rac -) forms of GTN also present significant cytotoxicity against a panel of cancer cell lines. ,,, Our group has also demonstrated the antiproliferative features of both enantiomerically pure ( R )- and ( S )-isomers as well as the rac -GTN form in an Ehrlich solid tumor model ( in vivo ), with no evidence of toxic effects or weight loss in the animals after the administered doses . More recently, it was reported that the treatment with rac -GTN delayed both the progression of prostatic preneoplastic lesions and prostate cancer in transgenic adenocarcinoma of the mouse prostate (TRAMP) model …”
Section: Introductionmentioning
confidence: 99%